An insight into the synthesis of cationic porphyrin-imidazole derivatives and their photodynamic inactivation efficiency against Escherichia coli - Moreira, Xavier (2020)
New porphyrin-imidazole derivatives were synthesised by Radziszewski reaction between 2-formyl-5,10,15,20-tetraphenylporphyrin 1 and several (hetem)aromatic 1,2-diones, which after cationization afforded promising monocationic photosensitizers 3a-d. Singlet oxygen studies have demonstrated that all the cationic porphyrin-imidazole conjugates 3a-d were capable to produce cytotoxic species. These photosensitizers were able to photoinactivate Eschericha coli and their inactivation profile was improved in the presence of KI.